Native Wolbachia infection and larval competition stress shape fitness and West Nile virus infection in Culex quinquefasciatus mosquitoes - Alomar, Abdullah A.; Pérez-Ramos, Daniel W.; Kim, Dongmin; Kendziorski, Natalie L.; Eastmond, Bradley H.; Alto, Barry W.; Caragata, Eric P. (Frontiers in Microbiology, 2023)
Wolbachia transinfections established in key mosquito vectors, including Aedes aegypti are typically associated with pathogen blocking - reduced susceptibility to infection with key pathogens and reduced likelihood those pathogens are transmitted to new hosts. Host-symbiont-virus interactions are less well understood in mosquitoes like Culex quinquefasciatus, which naturally harbor Wolbachia, with pathogen blocking observed in some populations but not others, potentially due to innate differences in their Wolbachia load. In nature, mosquito larvae are often subject to developmental stresses associated with larval competition, which can lead to reduced body size and differential susceptibility to arbovirus infection. In this study, we sought to understand whether competition stress and Wolbachia infection in Cx. quinquefasciatus combine to impact host fitness and susceptibility to infection with West Nile virus. We reared Wolbachia-infected and -uninfected Cx. quinquefasciatus larvae under three competition stress levels, increasing larval density without increasing the amount of food supplied. We observed that high competition stress extended development time, decreased the likelihood of eclosion, decreased body size, and increased susceptibility to WNV infection. We also observed that Wolbachia infection reduced WNV load under low competition stress, and significantly improved the rate of survival for larval reared under higher competition stress. Consequently, our data suggest that native Wolbachia infection in Cx. quinquefasciatus has differential consequences for host fitness and susceptibility to WNV infection depending on competition stress.